FOXO1-mediated autophagy regulation by miR-223 in sepsis-induced immunosuppression - Xiang, Guoan; Li, Qi; Lian, Di; Su, Chengcheng; Li, Xin; Deng, Shoulong; Xie, Lixin (Frontiers in Pharmacology, 2024)
Immunosuppression is the main cause of the high mortality rate in patients with sepsis. The decrease in the number and dysfunction of CD4+ T lymphocytes is crucial to the immunosuppressed state of sepsis, in turn affecting the development and prognosis of sepsis. Autophagy has been shown to play an important role in the immune imbalance exhibited during sepsis. In this study, we modulate the expression of miR-223 in CD4+ T lymphocytes, via the transfection of a mimic or an inhibitor of miR-223 to establish cell models of miR-223 overexpression and knockdown, respectively. Levels of autophagy were monitored using a double-labeled lentivirus (mRFP-GFP-LC3) and electron microscopy, and western blot analysis was used to estimate the levels of autophagy-related proteins and FOXO1 in the two cell models after co-treatment with lipopolysaccharide (LPS) and siRNA against FOXO1. We found that when the expression of miR-223 increased, FOXO1 expression decreased and autophagy decreased; whereas, when FOXO1 expression was inhibited, autophagy decreased significantly in different cell models after LPS induction. Thus, this study proved that miR-223 participate in the regulation of LPS-induced autophagy via the regulation of FOXO1 expression in CD4+ T lymphocytes which shed a new light for the diagnosis and treatment of sepsis.